Some factors affecting the abundance of phytoplankton in an unproductive alkaline lake (Lake Hazar, Turkey) - Kocer, Mehmet Ali Turan; Sen, Bulent (Tubitak Scientific & Technological Research Council Turkey, 2014)
This study aimed to explain the seasonal and vertical distribution of phytoplankton in the pelagic zone of a deep alkaline lake that is characterized by low phytoplankton abundance. Phytoplankton and water samples were collected seasonally from 9 points and 7 depths between the surface and 20 m from December 2004 to September 2005. Planktolyngbya contorta was the dominant or subdominant species in all seasons and depths. The dominance of Gomphonema species was observed in December, but they were subdominant in September. Cyclotella meneghiniana was dominant at 20 m and subdominant in the upper depths during March, June, and September. Melosira sp. and Meridion circulare were the dominant taxa of the surface phytoplankton in March and June, respectively. A nonparametric test showed the prevalence of cyanobacteria and green algae at a depth of 10 m. Principal component analysis showed the effect of temperature, pH, dissolved solids, nitrate, and silica on the abundance and distribution of phytoplankton. The generalized linear model revealed that high pH and high dissolved solids content seemed to affect the abundance of phytoplankton via limiting nutrient availability.
Keywords: Phytoplankton; distribution; external factors; principal component analysis; generalized linear model